SlyA Transcriptional Regulator Is Not Directly Affected by ppGpp Levels - Bartoli, Julia; Viala, Julie Pamela; Bouveret, Emmanuelle (Frontiers in Microbiology, 2020)
The SlyA transcriptional regulator controls the expression of genes involved in virulence and production of surface components in S. Typhimurium and E. coli. Its mode of action is mainly explained by its antagonism with the H-NS repressor for the same DNA binding regions. Interestingly, it has been reported that the alarmone ppGpp promotes SlyA dimerization and DNA binding at the promoter of pagC, enhancing the expression of this gene in Salmonella. A recurring problem in the field of stringent response has been to find a way of following ppGpp levels in vivo in real time. We thought that SlyA, as a ppGpp responsive ligand, was a perfect candidate for the development of a specific ppGpp biosensor. Therefore, we decided to characterize in depth this SlyA control by ppGpp. However, using various genes whose expression is activated by SlyA, as reporters, we showed that ppGpp does not affect SlyA regulation in vivo. In addition, modulating ppGpp levels did not affect SlyA dimerization in vivo, and did not impact its binding to DNA in vitro. We finally showed that ppGpp is required for the expression of hlyE in E. coli, a gene also activated by SlyA, and propose that both regulators are independently required for hlyE expression. The initial report of ppGpp action on SlyA might be explained by a similar action of SlyA and ppGpp on pagC expression, and the complexity of promoters controlled by several global regulators, such as the promoters of pagC in Salmonella or hlyE in E. coli.